A Fast-Track Care by a Nursing Case Management Concept Improved Status Epilepticus Outcomes. Issue 4 (August 2020) - Pranboon, Sineenard; Tiamkao, Somsak; Chainirun, Nanthaphan; Sawanyawisuth, Kittisak
ABSTRACT: BACKGROUND: Status epilepticus (SE) is an emergency neurological condition, which is life-threatening, results in high morbidity and mortality rates, and needs to be diagnosed and promptly cared for. This study aimed to develop and evaluate the SE fast-track care using a nursing case management concept on SE outcomes. METHODS: Quasi-experimental study conducted in adult patients with SE admitted in 15 emergency and intensive critical/intermediate care wards. SE outcomes were evaluated and compared between preintervention and postintervention. RESULTS: Time to treatment was reduced from 30 minutes to 3.5 minutes ( P < .001). Similarly, the seizure control rate increased from 65.7% to 94.4% ( P = .009). The mortality rate was reduced but did not reach statistical significance (8.6% vs 0%; P = .115). The intervention also reduced average waiting time for receiving antiepileptic drugs from the pharmacy department from 13.09 minutes to < 1 minute. CONCLUSION: The development of the fast-track care system for SE patients by nursing case management is at the core of management for coordinating multidisciplinary teams. This can improve outcomes by reducing the time to diagnosis and treatment time, therefore reducing mortality rates in SE patients.